Hubungan Stres Dengan Gangguan Siklus Haid - Era Nurpadila; Sri Kustiyati (Journal of Educational Innovation and Public Health, 2023)
Introduction: Stress is the body's non-specific response to load demands. During adolescence, unstable emotional changes occur due to hormonal fluctuations during the menstrual cycle. Teenage girls who experience irregular menstruation can be caused by changes in hormone levels due to stress or being in an emotional state. Objective: To determine the relationship between stress and menstrual cycle disorders in Islamic Middle School students at Amanah Ummah Mojolaban. Method: This research method is correlative analytic with a cross sectional design. The research subjects were 48 female high school students in grades 1, 2 and 3 of Amanah Ummah Mojolaban Islamic Middle School who met the inclusion and exclusion criteria. The sampling technique uses total sampling. Results: The majority of sample menstrual cycle disorders were abnormal (79.2%). The majority of sample stress was moderate stress (41.7%). The results of research using the Chi Square statistical test showed a value of (p=0.000) where the P value was smaller than significant (0.005), meaning there was a significant relationship between stress and menstrual cycle disorders. Conclusion: There is a significant correlation between stress and menstrual cycle disorders at Amanah Ummah Mojolaban Islamic Middle School.